Reputasi Sosial dan Etika Kepemimpinan Spiritual: Analisis Historis terhadap Legitimasi Kepemimpinan Nabi Muhammad - Dliya'uddin Achmad; Ahmad Musyafiq (Program Pascasarjana IAIN Langsa, 2025)
Existing studies on spiritual leadership often emphasize theological legitimacy or charismatic authority, while paying limited attention to the role of social reputation and ethical formation as foundational elements in the emergence of religious leadership. This gap highlights the need to examine how integrity and honesty function as forms of social capital that enable the transformation of individuals into recognized spiritual leaders. Accordingly, this study aims to analyze the role of social reputation and ethical preparation in establishing the legitimacy of spiritual leadership, with a primary focus on the Prophet Muhammad and a comparative perspective involving other religious figures. This research employs a qualitative methodology using historical and comparative approaches, based on the analysis of classical texts, historical archives, and relevant narrative sources. The findings demonstrate that a consistently maintained reputation for integrity and honesty constitutes a critical form of social capital that facilitates the transition from social roles to spiritual leadership. Moreover, mediation practices, economic engagement, and contemplative activities are identified as key factors that shape leaders’ ethical character and reinforce their legitimacy. This study contributes a holistic conceptual framework that integrates social capital theory with the study of spiritual leadership, thereby enriching the discourse in the sociology of religion and leadership ethics. The findings further imply that integrity and honesty are not merely personal virtues, but fundamental drivers of social trust, religious authority, and transformative leadership across diverse religious contexts.